Legal Certainty and Protection of Separate Property in Divorce Disputes: An Analysis of Supreme Court Decision No. 4557K/PDT/2024 - Akhirudin; Richard C. Adam (Al-Risalah, 2026)
In general, joint property is understood as property acquired by a married couple during their marriage, so that in the event of divorce, each party has the right to claim that property. If no property separation agreement was made before the marriage, disputes often arise during divorce regarding the ownership status of the property, with both the husband and wife claiming that the disputed property belongs to them. This situation highlights the legal uncertainty surrounding the separation of personal and joint property, particularly with regard to property received as a gift from the parents of one of the parties. The legal problem becomes even more complex because Law Number 1 of 1974 concerning Marriage does not provide detailed regulations regarding the difference between joint property and personal property, thus causing legal problems in court practice when gifts or presents are claimed as joint property. This study uses a normative legal research method with a legislative and case approach, specifically analyzing Supreme Court Decision Number 4557K/Pdt/2024. The results of the study show that the classification of property as joint property or separate property is largely determined by the existence of concrete evidence regarding the origin of the property. Legal protection for holders of separate property rights is strengthened through a convincing system of evidence to overcome the unpreparedness and limitations of existing normative regulations. Therefore, legal protection of property in divorce cases must be based on the principles of justice, legal certainty, and proportional evidence so that the rights of each party can be protected fairly.